UPPER CRETACEOUS PALEOMAGNETIC DATA FROM SHIKOTAN ISLAND, KURIL ARC: IMPLICATIONS FOR PLATE KINEMATICS - Bazhenov M.L.; Burtman V.S. (My University, 1994)
Maastrichtian tuffaceous sandstones and siltstones were sampled from four sites in the northern part of Shikotan Island in the Lesser Kuril Islands. A characteristic component (ChRM) isolated from most samples passes the reversal and fold tests and is most probably a primary remanence. The ChRM mean direction (D = 334°,I = 56°,k = 36,α95 = 3.2°) is14° ± 3.5° steeper than the Pacific reference direction and13 ± 4° more gentle than the Eurasian reference direction. We assume that the Lesser Kuril Islands together with their southwestern extension into the Nemuro Peninsula, Hokkaido were originally an island arc situated at about 36°N in the central-west Pacific. Soon afterwards, probably by the end of the Late Cretaceous, the Nemuro-Shikotan island arc became inactive and started moving with the Pacific plate. In the Miocene, about 15 m.y. ago, the Nemuro-Shikotan island arc collided with the Eurasian plate, overrode the subduction zone, and occupied its present-day position on the Pacific side of the Kuril island arc. Although this scenario fits the available paleomagnetic data and kinematics of the Pacific plate itself, it disagrees somewhat with the kinematic models for the North Pacific as a whole. In particular, by the end of the Late Cretaceous, the northern margin of the Pacific plate together with the extinct Nemuro-Shikotan island arc should have been in an area close to the transform or ridge-type Kula-Pacific boundary. The available paleomagnetic data from Northeast Asia, however, indicate that active islands arcs existed in mid-northern latitudes of the modern Pacific Ocean in the Cretaceous.
Keywords: Cretaceous; Mesozoic::Cretaceous; Мезозой::Меловая